Global Molecular Epidemiology of Cryptococcus neoformans and Cryptococcus gattii: An Atlas of the Molecular Types - Massimo Cogliati (Scientifica)
Cryptococcosis is a fungal disease affecting more than one million people per year worldwide. The main etiological agents of cryptococcosis are the two sibling species Cryptococcus neoformans and Cryptococcus gattii that present numerous differences in geographical distribution, ecological niches, epidemiology, pathobiology, clinical presentation and molecular characters. Genotyping of the two Cryptococcus species at subspecies level supplies relevant information to understand how this fungus has spread worldwide, the nature of its population structure, and how it evolved to be a deadly pathogen. At present, nine major molecular types have been recognized: VNI, VNII, VNB, VNIII, and VNIV among C. neoformans isolates, and VGI, VGII, VGIII, and VGIV among C. gattii isolates. In this paper all the information available in the literature concerning the isolation of the two Cryptococcus species has been collected and analyzed on the basis of their geographical origin, source of isolation, level of identification, species, and molecular type. A detailed analysis of the geographical distribution of the major molecular types in each continent has been described and represented on thematic maps. This study represents a useful tool to start new epidemiological surveys on the basis of the present knowledge.